Immigration Policy and Hispanics' Willingness to Run for Office - Catalina Amuedo-Dorantes; Jose R. Bucheli (Institute of Labor Economics (IZA), 2020)
For the first time in U.S. history, approximately 10 percent of the U.S. House of Representatives is Hispanic. The greater engagement of Hispanics in national politics has occurred after unprecedented growth in interior immigration enforcement disproportionately impacting Latinos. Using county-level data on all candidates running for congressional elections over the 2008–2018 decade, we find evidence of intensified immigration enforcement suppressing Hispanics' willingness to run for Congress. The effect, which is not present for female or Black minorities, is driven by local police-based measures, and more prevalent in localities without a sanctuary policy and in states with a Republican governor.
Keywords: D72; H0; J15; 330; diversity; electoral candidates; immigration enforcement; United States